The equation of motion of cotton fiber in the condenser - Mirzaumidov, Asilbek; Ganikhanov , Khusankhon; Mavlyanov , Aybek; Abdusamatov , Alisher (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This article is discussed the equation of motion of cotton fiber in the condenser, describing the motion of a fiber in a condenser, equations can be used that take into account the forces acting on the fiber, as well as the characteristics of the airflow and the interaction of the fiber with the surface of the condenser, calculating the value of the cross-sectional area, showed the dependence of the distance traveled by the fiber on the time in the condenser at the specified parameters